2018
DOI: 10.1186/s13148-018-0446-7
|View full text |Cite
|
Sign up to set email alerts
|

Endurance training remodels sperm-borne small RNA expression and methylation at neurological gene hotspots

Abstract: Remodeling of the sperm epigenome by lifestyle factors before conception could account for altered metabolism in the next generation offspring. Here, we hypothesized that endurance training changes the epigenome of human spermatozoa. Using small RNA (sRNA) sequencing and reduced representation bisulfite sequencing (RRBS), we, respectively, investigated sRNA expression and DNA methylation in pure fractions of motile spermatozoa collected from young healthy individuals before, after 6 weeks of endurance training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 43 publications
5
73
0
1
Order By: Relevance
“…For example, the sperm RNA signature could be used as a clinical marker of offspring metabolic disease susceptibility. In addition, as human sperm RNA profiles are known to be efficiently altered by improved body condition 1,[83][84][85] , the signature could be monitored before a planned pregnancy and clinical guidance (such as improvements to lifestyle) could also be introduced if necessary to reshape the sperm RNA code towards a healthy condition (Fig. 3).…”
Section: Application and Precision Medicinementioning
confidence: 99%
“…For example, the sperm RNA signature could be used as a clinical marker of offspring metabolic disease susceptibility. In addition, as human sperm RNA profiles are known to be efficiently altered by improved body condition 1,[83][84][85] , the signature could be monitored before a planned pregnancy and clinical guidance (such as improvements to lifestyle) could also be introduced if necessary to reshape the sperm RNA code towards a healthy condition (Fig. 3).…”
Section: Application and Precision Medicinementioning
confidence: 99%
“…Collectively, from the studies summarised in Table 1, it is now apparent that an array of paternal stressors, ranging from dietary perturbation (e.g. high fat, low protein), chronic psychological stress, ethanol consumption, environmental pollution and cigarette smoke exposure, can each differentially alter the sRNA profile of sperm of exposed males , Marczylo et al 2012, Rodgers et al 2013, Saavedra-Rodriguez & Feig 2013, Gapp et al 2014, Metzler-Guillemain et al 2015, Paris et al 2015, de Castro Barbosa et al 2016, Donkin et al 2016, Fullston et al 2016, Murashov et al 2016, Rompala et al 2016, Sharma et al 2016, Short et al 2016, Benito et al 2018, Dickson et al 2018, Ingerslev et al 2018, Rompala et al 2018. Further, some of these studies went on to demonstrate that an altered sperm sRNA profile contributed to altered phenotypic outcomes in the offspring post fertilisation.…”
Section: The Role Of Epididymosomes In Mediating An Altered Small Rnamentioning
confidence: 99%
“…Several other studies have demonstrated that nutritional status, physical activity levels, endocrine disruptors, and stress can alter sperm epigenetics. [62][63][64] The implications of these findings are intriguing as we are not only learning that environmental factors can alter epigenetic programming, but we are also discovering that this epigenetic reprogramming can be transmitted to offspring. This begs the question about the impact of common vices of men on sperm epigenetic reprogramming and potential transmission to offsprings.…”
Section: Offspring Somatic Health and Transgenerational Effectsmentioning
confidence: 99%